Suicide Ideation and Neurocognition Among 9- and 10-Year Old Children in the Adolescent Brain Cognitive Development (ABCD) Study. Issue 2 (3rd April 2022) - Huber, Rebekah S.; Sheth, Chandni; Renshaw, Perry F.; Yurgelun-Todd, Deborah A.; McGlade, Erin C.
Abstract: Objective: During the past decade, the pediatric suicide rate has nearly tripled. Yet, little is known about suicide behavior (SB) in children. Identification of risk factors associated with SB during childhood may be critical to preventing future attempts. The purpose of this study was to examine the relationship between neurocognitive performance and suicide ideation (SI) in children. Method: The present study utilized baseline data from 11, 875 participants in the Adolescent Brain Cognitive Development (ABCD) study, a longitudinal study that follows 9- and 10-year-old children through late adolescence to examine factors that influence developmental trajectories. Suicidality was assessed by the Kiddie Schedule for Affective Disorder and Schizophrenia (KSADS) suicide module completed by the parent. Neurocognitive ability was assessed using the NIH Toolbox Cognition measures administered to the youth. Results: Children with a history of SI reported by their parent or concordant parent and youth report of SI demonstrated lower performance on the NIH Toolbox Picture Sequence Memory Test compared to children without SI. The difference in performance on the memory task remained significant when including demographic characteristics, family history of suicide, and internalizing symptoms in the model as covariates. Conclusions: To our knowledge, this is the first study to identify decreased episodic memory in children with SI. These findings are similar to results from adult and adolescent studies which have reported decreased memory performance among suicide attempters. Deficits in episodic memory may impact a child's ability to problem-solve and generate potential future outcomes, which may increase the risk for SB. Early identification of memory deficits in children may inform suicide prevention and intervention efforts. Highlights: 6% of parents and children reported a history of active suicide ideation in children. Children with a history of suicide ideation had lower episodic memory performance. Early identification of memory deficits may inform suicide intervention efforts.